Acculturation of Javanese culture with Islamic culture in the month of Muharrom in Brayo Village Wonotunggal Batang - Maya Ika Trisnawati; Hana Dian Malasari; Alvian Varihul Mustavid; Khoirunnisah Harahap; Tsabita Imania Yusrika (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Nyadran is a series of traditional ceremonies, which are part of cultural heritage and believe that certain places are sacred or holy places. Nyadran traditions like this are a from of salvation carried out as a from of gratitude and respect for ancestors. The data collection technique used in this research was interviews with the main sources, the head of the Nyadran committee and the of Brayo village. The location of this research was in Ujung Biru Hamlet, Brayo Village, Wonotunggal District. Nyadran activities in Ujung Biru Hamlet are held in the month of Muharrom because Muharrom is not the Hijri New Year. Nyadran implementation in Brayo Village has been carried out since ancient times, as time goes by, the nyadran tradition has undergone many changes.